2018
DOI: 10.1590/1806-9282.64.03.217
|View full text |Cite
|
Sign up to set email alerts
|

Selenium supplementation in pediatric patients using parenteral nutrition: Is it time to do something?

Abstract: Lower plasma selenium levels have been detected since the start of the research and supplementation (2 µg/kg/day of selenous acid) was not to enough to approach the reference values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…24 Forty-five preterm infants (n = 77; 58.4%) and 10 term infants (n = 25; 40%) were deficient of selenium. Like previous studies, 18,19 selenium deficiency tended to be higher in preterm infants (P = .108). The supply of selenium from the mother to the fetus increases in the third trimester of pregnancy.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…24 Forty-five preterm infants (n = 77; 58.4%) and 10 term infants (n = 25; 40%) were deficient of selenium. Like previous studies, 18,19 selenium deficiency tended to be higher in preterm infants (P = .108). The supply of selenium from the mother to the fetus increases in the third trimester of pregnancy.…”
Section: Discussionsupporting
confidence: 79%
“…Several previous studies showed that a supply of 1.34-3 mcg/kg/day of selenium is insufficient for infants, especially preterm infants. 6,18,19,36,37 According to Darlow et al, 15 whose study was the basis for the revised the European Society for Clinical Nutrition and Metabolism (ESPEN) guidelines, the plasma selenium level of very lowbirth-weight infants (VLBWIs) supplemented with 7 mcg/kg/day of selenium as PN can increase to healthy term infants' plasma selenium levels. The study of Darlow et al 15 was conducted in New Zealand, where selenium concentrations are lower than in other regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Selenium deficiency in infants most commonly occurs in preterm infants [10,11], in whom the storage capacity of selenium in the liver is limited compared to that of term ACNM infants. In addition, selenium is depleted quickly with rapid growth [12].…”
Section: Introductionmentioning
confidence: 99%